The last PEG or community media 2.0? Negotiating place and placelessness at PhillyCAM. (January 2014) - Ali, Christopher
This article investigates the changes, challenges and opportunities present in American community media through a case study of PhillyCAM, a community television/media center in Philadelphia, PA. From this ethnographic study, it is suggested that community media navigate the tensions between television and digital media/user-generated content through reliance on place and liveness. In shifting from 'community television' to 'community media' these organizations are able to situate themselves as dynamic components in a local and participatory media ecosystem, develop new programs and strategic partnerships, and differentiate themselves from other organizations, while remaining consistent with their original mandates.